Mechanism of sorafenib resistance associated with ferroptosis in HCC - Guo, Lingling; Hu, Cuntao; Yao, Mengwen; Han, Guang (Frontiers in Pharmacology, 2023)
Hepatocellular carcinoma (HCC) is the most familiar primary hepatic malignancy with a poor prognosis. The incidence of HCC and associated deaths have risen in recent decades. Sorafenib is the first drug to be approved by the Food and Drug Administration (FDA) for routine use in the first-line therapy of patients with advanced HCC. However, only about 30% of patients with HCC will get benefit from sorafenib therapy, and drug resistance typically develops within 6 months. In recent years, the mechanisms of resistance to sorafenib have gained the attention of a growing number of researchers. A promising field of current studies is ferroptosis, which is a novel form of cell death differing from apoptosis, necroptosis, or autophagy. This process is dependent on the accumulation of intracellular iron and reactive oxygen species (ROS). Furthermore, the increase in the intracellular iron level and ROS can be significantly observed in cells resistant to sorafenib. This article reviews the mechanisms of resistance to sorafenib related to ferroptosis, evaluates the relationship between ferroptosis and sorafenib resistance, and explores new therapeutic approaches capable of reversing sorafenib-resistance in HCC through modulation of ferroptosis.